Ampulla of Vater Carcinoma: Sequencing Analysis Identifies TP53 Status as a Novel Independent Prognostic Factor and Potentially Actionable ERBB, PI3K, and WNT Pathways Gene Mutations. Issue 1 (January 2018) - Mafficini, Andrea; Amato, Eliana; Cataldo, Ivana; Rusev, Borislav C.; Bertoncello, Luca; Corbo, Vincenzo; Simbolo, Michele; Luchini, Claudio; Fassan, Matteo; Cantù, Cinzia; Salvia, Roberto; Marchegiani, Giovanni; et al.
Abstract : Objective: To identify molecular prognostic factors and potentially actionable mutations in ampulla of Vater cancer (AVC). Background: The largely variable outcomes of AVCs make clinical decisions difficult regarding the need of postsurgical therapy, which is based on morphological and immunohistochemical classification that do not adequately consider the varying degrees of heterogeneity present in many AVCs. No approved targeted therapies for AVC exist, but some show promising results requiring better molecular characterization to identify potential responders. Methods: We assessed 80 AVCs for the prognostic value of mutations of kirsten rat sarcoma ( KRAS ), neuroblastoma RAS ( NRAS ), B rapidly accelerated fibrosarcoma ( BRAF ), TP53, and 4 membrane erythroblastosis oncogene B ( ERBB ) receptor tyrosine kinases ( EGFR-ERBB1, HER2-ERBB2, HER3-ERBB3, HER4-ERBB4 ) amenable to pharmacological inhibition. Moreover, we evaluated mutations in 16 key components of rat sarcoma (RAS), phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K), protein 53 (P53), transforming growth factor beta (TGF-β), and wingless/integrated (WNT) pathways, recently associated to AVC by whole-exome sequencing. Results: TP53 and KRAS were mutated in 41% and 35% of cases, respectively, and emerged as independent prognostic factors together with tumor stage and regardless of the histotype ( TP53 : P = 0.0006; KRAS : P = 0.0018; stage IIB: P = 0.0117; stage III–IV: P = 0.0020). ERBB, WNT and PI3K pathway genes were mutated in 37.5% of cases. Conclusions: KRAS and TP53 mutations are negative predictors of survival in AVCs, regardless of histotype. Potentially actionable mutations in ERBB, WNT, and PI3K signaling pathway genes are present in 37.5% of all cases. These might be amenable to target therapy using available drugs like Everolimus in PI3K-mutated cases or compounds under active screening against ERBB and WNT signaling. Abstract : Supplemental Digital Content is available in the text